Десять тисяч негативів унікального фотоархіву - Селівачов, М. (Народна творчість та етнографія, 2006)
The author of the article speaks on an impressive photographical archive containing a collection of glass negatives. The history of the collection from the period of its oblivion to its detailed research and systematizing is depicted. The negatives bring through the years a great amount of ethnographical materials, such as the images of Ukrainian scenery, folk costumes, archaeological finds, etc.